Raja', Ammatul-Salam Ahmad. “Arab Women: Between Societal Norms and the Fundamentals of Islam,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 155-180. - رجاء, أمة السلام أحمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2004)
Ammatul-Salam Raja’ discusses the subject of women, holding that the subject is influenced by either of two factors, negative cultural innovations or perverted practices. She contends that traditions and conventions came to control society’s view of women and dealing with issues pertaining to women in a manner that conflicted with the fundamentals and precepts of the Shariʿah. Her research adopts a ta’ṣīlī approach (a framework established upon referral to principal Islamic sources) in order to illustrate the relationship between social conventions and law in dealing with women issues; addressing definitions of terms, types of conventions, the relationship between convention and Shariʿah, and presenting paradigms of conventions prevailing in classical and modern times in Arab societies, including exposing their violations of the precepts of Shariʿah. It concludes that the Shariʿah overrides and dominates conventions; therefore, whatever is in accordance with Shariʿah is legal, and whatever contradicts it is invalid.